Micobiota parásita de ambientes acuáticos de la provincia de Buenos Aires - Steciow, Mónica Mirta (2008)
Zoosporic fungi (Chytridiomycota, Hyphochytridiomycota and Peronosporomycota) include organisms that occur as saprotrophs on vegetable debris or as parasites of invertebrates, plants, algae and of other zoosporic fungi. Water samples and floating organic matter were collected during a 2005-2006 survey at Las Cañas stream and Villa Elisa channel (Reserva Natural Selva Marginal Punta Lara, Pdo. de Ensenada, Bs. As.), and samples were processed with the baiting technique. Six taxa of parasitic zoosporic fungi were recovered: Olpidium sp. (Braun) Rabenhorst, Chytridium sp. Braun and Rhizophydium carpophyllum (Chytridiomycota), Rhizidiomyces apophysatus and R. hirsutus (Hyphochytridiomycota), Olpidiopsis pythii (Butler) Karling and Dictyuchus sp. Leitgeb, (Peronosporomycota). Olpidiopsis pythii is the first record for Argentina and South America.